Tingkat Kejadian Escherichia coli Penghasil Extended Spectrum Β-Lactamase yang Diisolasi dari Feses Broiler di Kota Bogor - Cholilia Abadiatul Masruroh; Mirnawati Bachrum Sudarwanto; Hadri Latif (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
The use of antibiotics in food-producing animals may encourage the occurence of bacterial resistance named Escherichia coli that produces Extended Spectrum β-lactamase (ESBL). Antibiotical resistance is an important issue in the animal health and human health. This study focused on the presence of ESBL-producing E.coli in chicken feces. The number of sample feces was 100. E. coli isolates were obtained from broiler chicken feces in Bogor. Isolates obtained were identified using API 20E kit. Confirmation of ESBL in this study used Double disc method using antibiotical disc namely cefpodoksim, ceftazidime and cefotaxime. The existence ofESBL-producing E. coli which isolated from the feces of broiler chickens in the city of Bogor is 25% (4/16).